2018
DOI: 10.1038/s41433-018-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Tonometers—which one should I use?

Abstract: Although several factors are known to play a role in the development and progression of glaucoma, intraocular pressure (IOP) remains the only modifiable risk factor. Medical and surgical treatments for glaucoma both aim to reduce IOP to minimize disease progression. Tonometry is therefore an essential element of the ophthalmological exam. There are several types of tonometers available currently. These range from well-established instruments that have been in clinical use for decades to new devices, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 74 publications
0
26
0
1
Order By: Relevance
“…NCT is more affected by CCT than the GAT, which may be justified by the corneal viscoelastic property, where the rate of impingement of force affects the stiffness 47 .…”
Section: Discussionmentioning
confidence: 99%
“…NCT is more affected by CCT than the GAT, which may be justified by the corneal viscoelastic property, where the rate of impingement of force affects the stiffness 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Other methods to measure IOP include indentation tonometry, rebound tonometry, pneumotonometry, and a variety of newer methods, each of which have advantages and disadvantages. 8 At the present time, there is no means to directly measure the orbital CSF pressure. ICP is typically measured by a lumbar puncture (LP).…”
Section: Definition and Physiological Implicationsmentioning
confidence: 99%
“…12 Other studies in the literature reported other factors related to corneal biomechanical parameters also could affect IOP measurements. [13][14][15][16] A thinner CCT has been reported to represent a significant risk in patients diagnosed with primary openangle glaucoma; moreover, patients having thinner CCT were found to have more advanced pathology and a severe glaucomatous defect. 5,17 Ultrasound pachymetry has been a universally accepted tool for measuring CCT, being highly reproducible and consistent.…”
Section: Introductionmentioning
confidence: 99%